What the stories of the Paris 2024 Olympics tell us about how we could enter a new era of medical education - Rakesh Patel (Future Healthcare Journal)
The Paris 2024 Olympics marked a return to normal for the Games following the disruption caused by the pandemic, but they also heralded a new era for the global community in terms of events and competition. At the core of the Games were the athletes, each with their individual story based on their own experience and set of circumstances. Reflecting on these stories in the context of medical education emerges a narrative that can be applied to our athlete equivalents – medical students and resident doctors. The purpose of the reflection is to trigger a conversation about what our new era of medical education should look like – the things that we should continue doing, the things we could look to do differently, and the things we should look to stop doing.